Linking black hole growth with host galaxies: the accretion–stellar mass relation and its cosmic evolution. Issue 2 (27th October 2017) - Yang, G; Brandt, W N; Vito, F; Chen, C-T J; Trump, J R; Luo, B; Sun, M Y; Xue, Y Q; Koekemoer, A M; Schneider, D P; Vignali, C; Wang, J-X
Abstract: Previous studies suggest that the growth of supermassive black holes (SMBHs) may be fundamentally related to host-galaxy stellar mass ( M ⋆ ). To investigate this SMBH growth– M ⋆ relation in detail, we calculate long-term SMBH accretion rate as a function of M ⋆ and redshift [BHAR(M_, z) ] over ranges of log ( M ⋆ /M⊙ ) = 9.5–12 and z = 0.4–4. Our BHAR(M_, z) is constrained by high-quality survey data (GOODS-South, GOODS-North and COSMOS), and by the stellar mass function and the X-ray luminosity function. At a given M ⋆, BHAR is higher at high redshift. This redshift dependence is stronger in more massive systems [for log ( M ⋆ /M⊙ ) ≈ 11.5, BHAR is three decades higher at z = 4 than at z = 0.5], possibly due to AGN feedback. Our results indicate that the ratio between BHAR and average star formation rate (SFR ) rises towards high M ⋆ at a given redshift. This BHAR/SFR dependence on M ⋆ does not support the scenario that SMBH and galaxy growth are in lockstep. We calculate SMBH mass history [ M BH ( z )] based on our BHAR(M_, z) and the M ⋆ ( z ) from the literature, and find that the M BH – M ⋆ relation has weak redshift evolution since z ≈ 2. The M BH / M ⋆ ratio is higher towards massive galaxies: it rises from ≈1/5000 at log M ⋆ ≲ 10.5 to ≈1/500 at log M ⋆ ≳ 11.2. Our predicted M BH / M ⋆ ratio at high M ⋆ is similar to that observed in local giant ellipticals, suggesting that SMBH growth from mergers is unlikely to dominate over growth from accretion.